Impact of bisphosphonate drugs on dental implant healing and peri-implant hard and soft tissues: a systematic review - Luca Fiorillo; Marco Cicciù; Tolga Fikret Tözüm; Cesare D'Amico; Giacomo Oteri; Gabriele Cervino (BMC, 2022)
Abstract Objective Implantology represents the gold standard for oral rehabilitation, unfortunately, often, despite there are no local contraindications to this type of rehabilitation, there are uncertainties regarding the general health of our patients. Many patients nowadays take bisphosphonate drugs, often without first seeking advice from an oral surgeon or a dentist. The purpose of this review is precisely to highlight any contraindications to this type of treatment reported in the literature, in patients who take or have taken bisphosphonate drugs. Methods For this study the scientific information sources were consulted using as search terms "("bisphosphonate AND "dental implant")", obtaining 312 results, these were subsequently skimmed according to the inclusion and exclusion criteria, and further evaluated their relevance to the study and the presence of requested outcomes. Results Only 9 manuscripts (RCTs, Multicentric studies and Clinical Trials) were included in this review, as they respected the parameters of this review, they were analyzed and it was possible to draw important results from them. Surely from this study it is understood that the use of bisphosphonate drugs does not represent an absolute contraindication to implant therapy, it is evident how adequate pharmacological prophylaxis, and an adequate protocol reduce the risks regarding implant failures. Furthermore, the values of marginal bone loss over time seem, even if not statistically significant, to be better in implant rehabilitation with bisphosphonate drugs association. Only a few molecules like risedronate, or corticosteroids, or some conditions like smoking or diabetes have shown a high risk of surgical failure. Conclusion Although this study considered different studies for a total of 378 patients and at least 1687 different dental implants, showing better results in some cases for dental implant therapy in cases of bisphosphonate intake, further clinical, randomized and multicentric studies are needed, with longer follow-ups, to fully clarify this situation which often negatively affects the quality of life of our patients and places clinicians in the face of doubts.